2012
DOI: 10.3174/ajnr.a3277
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine MR Imaging Findings of Patients with Hirayama Disease in North America: A Multisite Study

Abstract: BACKGROUND AND PURPOSE:Most studies of HD have been conducted in Asia, particularly Japan. To characterize the MR imaging findings of North American patients with HD, we reviewed neutral and flexion cervical MR imaging examinations performed for possible HD at 3 academic medical centers located in the Southeastern, Southwestern, and Midwestern regions of the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
54
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 15 publications
4
54
0
1
Order By: Relevance
“…Nevertheless this sign is not always present in HD patients. Zhou et al and Lheman et al reported a prevalence respectively of 71% and 76% (10,35). Interestingly, Lai et al (36) demonstrated the presence of anterior shifting of posterior dural sac in 46% of healthy subjects, of a lesser degree compared to patients group and without evidence of cord compression.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless this sign is not always present in HD patients. Zhou et al and Lheman et al reported a prevalence respectively of 71% and 76% (10,35). Interestingly, Lai et al (36) demonstrated the presence of anterior shifting of posterior dural sac in 46% of healthy subjects, of a lesser degree compared to patients group and without evidence of cord compression.…”
Section: Discussionmentioning
confidence: 97%
“…CF has a various prevalence in different case series. Yin et al, Hassan et al and Raval et al (6,27,31) reported a 100% of prevalence while Lehman et al (10) and Yang et al (32) found it respectively in 48% and 43%. Finsterer et al (9) executed MRI studies in the neutral position and reported asymmetric CF only in one patient of seven.…”
Section: Discussionmentioning
confidence: 97%
“…Insufficient growth of the dura relative to the spine during adolescence causes forward displacement of the dura in flexed positions of the cervical spine. 6 The subsequent compression of the spinal cord against the vertebral bodies compromises microcirculation. 7 In the slowly progressing Hirayama syndrome, damage to the cord parenchyma is confined to the anterior horn of the spinal cord gray matter with consecutive flaccid paresis in the upper extremities.…”
Section: Discussionmentioning
confidence: 99%
“…The disappearance of physiological lordosis of the cervical vertebrae was reported by Hashimoto et al 9 in 11 of 15 patients, Sonwalkar et al 10 in 6 of 8 patients, Raval et al 11 in 9 of 9 patients and Hassan et al 12 in 10 of 11 patients. Abnormal cervical curvature is an important finding on the cervical MRI for the diagnosis of Hirayama disease 13. Masaki et al 14 performed posterior fixation in patients with cervical kyphosis, which resulted in the relief of symptoms.…”
Section: Discussionmentioning
confidence: 99%